Removal of Alizarin Yellow and Murexide Dyes from Water Using Formalin Treated Pisum sativum Peels - Rehman, Rabia; Mahmud, Tariq; Arshad, Ayesha (Asian Journal of Chemistry, 2015)
Adsorption process is eco-friendly which is used for the removal of dyes. In this research work, formalin treated Pisum sativum peels were used for the removal of Murexide and Alizarin yellow from water. Various parameters like adsorbent dose, pH, temperature, agitation speed and contact time were investigated. Three isotherms Freundlich, Langmuir and Temkin were used to elucidate the observed adsorption phenomenon. Freundlich adsorption isotherm was best fitted with maximum removal of 2.47 and 11.04 mg/g of Alizarin yellow and Murexide, respectively. From this research work, it is concluded that peels of Pisum sativum were proved efficient and effective adsorbents for the removal of Alizarin yellow and Murexide.